-15=6+7y

Simple and best practice solution for -15=6+7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=6+7y equation:


Simplifying
-15 = 6 + 7y

Solving
-15 = 6 + 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
-15 + -7y = 6 + 7y + -7y

Combine like terms: 7y + -7y = 0
-15 + -7y = 6 + 0
-15 + -7y = 6

Add '15' to each side of the equation.
-15 + 15 + -7y = 6 + 15

Combine like terms: -15 + 15 = 0
0 + -7y = 6 + 15
-7y = 6 + 15

Combine like terms: 6 + 15 = 21
-7y = 21

Divide each side by '-7'.
y = -3

Simplifying
y = -3

See similar equations:

| 4x+5+5x+22=90 | | (X/5)=-13 | | 4k=6k-6 | | 4k=6k-2 | | 48.3(8/25)2 | | a+2=-12 | | 3y+2=y+11 | | 4x^2-32x+20=0 | | 7-4s-1=-3s-4 | | 9y+5x=37 | | -2x+49=2x+13 | | -4h=40 | | -2+17-5=0 | | -3x+1=x+13 | | -6-4g=10-2g | | 9=(v/7) | | 2(-2x+17)=0 | | -5=2y+1 | | 16=0.5X+6 | | =9-5 | | 9=2+b | | 2(-2-4p)+2(-2p-1)=0 | | 12=-4+y | | 6x=(x+2)8+6 | | -11=-2+-1y | | (v/6)=13 | | 3y^2-12y+15=0 | | 4+9n=6n+4 | | (4a^2-7a+12)(a^2+2a-3)= | | 6+a=49 | | .5+.666p+6=4p-1-.8333p | | 3(-6-6x)=198 |

Equations solver categories